Effects of transformer’s turn ratio mismatch towards the performance of dual active bridge converter - Suliana, Ab Ghani; Hamdan, Daniyal; Nur Huda, Ramlan; Tiong, Meng Chung (2018)
This paper presents the study of the effect of transformer’s turn ratio mismatch on the performance of dual active bridge (DAB) converter. DAB converter was part of the components of a solid state transformer (SST) where it provides galvanic isolation as well as interface systems with different voltage level. In this study, a DAB circuit was developed and the performance was examined in both MATLAB Simulation and hard-ware-in-the-loop (HIL) simulation. The DAB system was examined under five different transformer ratio. The behavior of the DAB shows a comparable results under both test platform. The real-time performance of DAB converter has shown an efficiency up to 95.91 %.